Comparative typological features of segmental phono-stylistic means in words of foreign language origin in Russian and Uzbek languages - Otaboyevna, Kunduz Saparova (Linguistics and Culture Review, 2021)
This research is devoted to the analysis of stylistic peculiarities of phonovariants of words of foreign origin in Russian and Uzbek. It is aimed at the investigation of the stylistic values of phonovariants of the borrowed words in the Russian and Uzbek languages and substantiation of the isomorphic and allomorphic features of such language units in comparison. So as to achieve the aim of the research, several objectives of the research are set: identification of the current status of the research problem; review of related literature; analysis of stylistic peculiarities of phonovariants of the words of foreign origin in compared languages; substantiation of isomorphism and allomorphism of honostylistic features of borrowed words in Russian and Uzbek; discussion of stylistic potential of phonovariants of the words of foreign origin in compared languages.